Learning Management In Increasing The Quality Of Graduates At Aliyah Boarding Schools In Banten Province (Study on MAN Insan Cendekia and MAN 2 Serang) - Rojak, Abdul; Wasliman, Iim; Koswara, Nandang; Karim Fatkhullah, Faiz (International Journal of Educational Research & Social Sciences, 2022)
The purpose of this community service was to educate the application of probiotics and immunostimulants in aquaculture. This activity was carried out in Cot Darat village, Samatiga District, West Aceh Regency. This activity is divided into three steps, namely: (1) Introduction and socialization of probiotics and immunostimulant; (2) practice to produce probiotics and the application techniques; and (3) the monitoring of fish health and growth during cultivation. The type of bacteria used in this probiotic is Lactobacillus bacteria and the immunostimulant ingredients are turmeric and curcumin. Lactobacillus, turmeric and curcuma are known can improve fish health in aquaculture. The results of this activity indicate that group members have understood the definition of probiotics and immunostimulants, their benefits and how to make and apply them in aquaculture. In addition, fish health and growth are increase during fish culture compare before the probiotics was applied. The differences that occurred during probiotics application in fish cultivation were seen that the fish became healthier, the growth was better, and fish mortality decreased.